2017
DOI: 10.1039/c7ra07534k
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured carbon–metal hybrid aerogels from bacterial cellulose

Abstract: Nanostructured carbon–metal hybrid aerogels by carbothermal reduction of nickel or iron hydroxide inside bacterial cellulose at remarkably low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In fact, the I D /I G value is significantly lower than the one of the commercial activated carbon Norit (1.92) . The spectrum of AH‐Enz‐py also displayed the 2D band at 2670 cm −1 , which is generally associated with the stacking order of graphene planes . The absence of this band in OSL‐py is a clear indication of the higher graphitic organization in AH‐Enz‐py, which is possibly related to the higher cellulose content in this residue.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In fact, the I D /I G value is significantly lower than the one of the commercial activated carbon Norit (1.92) . The spectrum of AH‐Enz‐py also displayed the 2D band at 2670 cm −1 , which is generally associated with the stacking order of graphene planes . The absence of this band in OSL‐py is a clear indication of the higher graphitic organization in AH‐Enz‐py, which is possibly related to the higher cellulose content in this residue.…”
Section: Resultsmentioning
confidence: 81%
“…[45] The spectrum of AH-Enz-py also displayed the 2D band at 2670 cm À 1 , which is generally associated with the stacking order of graphene planes. [13] The absence of this band in OSL-py is a clear indication of the higher graphitic organization in AH-Enz-py, which is possibly related to the higher cellulose content in this residue. This is somewhat opposed to findings reported by Deng et al [34] that observed a slightly higher graphitic degree of KHCO 3 activated carbon from alkaline lignin as compared to αcellulose.…”
Section: Biochars From Side-stream Ligninsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, long synthesis route and aging at 100°C for a prolonged period (24 hr) were utilized to form BC nickel hybrid. Moreover, the deposition of nickel contents on BC was in the form of fused particles rather than homogeneous coating having hierarchical structure to increase the specific surface area …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the deposition of nickel contents on BC was in the form of fused particles rather than homogeneous coating having hierarchical structure to increase the specific surface area. 36 Motivating with the overall performance of the aforementioned methods, herein, we are proposing a simple and solution-based method for growing hierarchical nickel oxyhydroxide (NiOOH) on the surface of BC (BC-NiOOH). Furthermore, the in situ formation mechanism is observed through confocal microscopy for the first time to study the formation of composite in the hydrogel form and proposed a formation mechanism of NiOOH on the nanofibers of BC in the form of hydrogel.…”
mentioning
confidence: 99%